EFFECT OF SUPPLEMENTARY LIGHT ON GROWTH, FLOWERING AND CUT FLOWER QUALITY IN TWO CULTIVAR OF CARNATION PLANT - Layla S. M. AL-Mizory,; Yousif H. Hammo, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to investigate the effects of different types of light and some factors on some vegetative growth and flowering of two cultivars of carnation plant (Dianthus caryophyllus L.). The results showed the maximum leaves number, leaf area per plant, internodes number and intermodal length were recorded under 14h incandescent (41.09 leaves/plant, 363.91 cm2, 18.70 node/plant, and 7.675 cm) respectively, and the increase was significant. While the effect of triple interaction, which showed a significant effect in all characteristics, the largest leaf area per plant (578.66 cm2) was obtained from the moonlight cultivar when cultured on the media containing 60% local compost and exposed to the 14h incandescent, Also, the maximum vase life was found in the Ormea cultivar (17.47 days) when the cultivar was exposed to the 14h incandescent and was cultured on medium that included 60% local compost. The best grade flower was obtained when the Ormea cultivar was cultured on a medium containing 30% and 60% local compost under 14 hours of incandescent light, reaching 3.89.